2021
DOI: 10.3390/geriatrics7010008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Dementia Support Programs with Multicultural and Multilingual Populations

Abstract: Background: Dementia care programs have become more common due to a growing number of persons living with dementia and lack of substantial benefit from pharmacologic therapies. Cultural and language differences may present barriers to access and efficacy of these programs. In this article, we aimed to systematically review the current literature regarding outcomes of dementia care programs that included multicultural and non-English speaking populations. Methods: A systematic review was conducted using four sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Improved tools and measures to personalize services for caregivers to maximize their benefits represent an emerging area of research [580][581][582][583][584][585]. More studies are also needed to adapt proven interventions or develop new intervention approaches for families from different racial, ethnic and socioeconomic backgrounds and in different geographic settings 427,[586][587][588][589][590][591][592][593][594]. Additional research on interventions focused on disease stages is also required, as is research on specific intervention needs for LGBT caregivers for whom a lack of inclusive practices on the part of health care professionals, stigma, and a reluctance to seek support may result in greater unmet needs compared with non-LGBT dementia caregivers 595,596.…”
mentioning
confidence: 99%
“…Improved tools and measures to personalize services for caregivers to maximize their benefits represent an emerging area of research [580][581][582][583][584][585]. More studies are also needed to adapt proven interventions or develop new intervention approaches for families from different racial, ethnic and socioeconomic backgrounds and in different geographic settings 427,[586][587][588][589][590][591][592][593][594]. Additional research on interventions focused on disease stages is also required, as is research on specific intervention needs for LGBT caregivers for whom a lack of inclusive practices on the part of health care professionals, stigma, and a reluctance to seek support may result in greater unmet needs compared with non-LGBT dementia caregivers 595,596.…”
mentioning
confidence: 99%
“…Another systematic review reported preliminary evidence to support the acceptability of psychosocial interventions by dementia caregivers, although the available supporting evidence was limited (Dam et al ., 2016). A third systematic review of dementia care programs commented on limitations of the literature, although there seemed to be some positive effect on providing support and improving outcomes for persons living with dementia and their caregivers (Demanes et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 631 , 632 , 633 , 634 , 635 , 636 More studies are also needed to adapt proven interventions or develop new intervention approaches for families from different racial, ethnic and socioeconomic backgrounds and in different geographic settings. 436 , 461 , 637 , 638 , 639 , 640 , 641 , 642 , 643 , 644 Additional research on interventions focused on disease stages is also required, as is research on specific intervention needs for LGBT caregivers for whom a lack of inclusive practices on the part of health care professionals, stigma, and a reluctance to seek support may result in greater unmet needs compared with non‐LGBT dementia caregivers. 438 , 645 , 646 …”
Section: Caregivingmentioning
confidence: 99%